Stress-strain model for compressive fracture of RC columns confined with CFRP jackets - Turgay, T.; Koksal, H. O.; Karakoc, C.; Polat, Z. (TAYLOR & FRANCIS LTD, 2007)
Catastrophic earthquakes with quite short periods often occur in Turkey. This fact necessitates and paves the way to the preparations of earthquake scenarios of the existing building stock including structures not properly constructed against earthquakes with loss estimations. There are so many buildings in densely populated areas of Turkey and many other earthquake prone countries needing urgent rehabilitation and strengthening. The use of external FRP jackets can provide confinement for RC columns in a fast and efficient way and improve their performance significantly during an earthquake. The noticeable increase in the compressive strength and ductility of concrete is the main reason for the use of FRP jackets in the seismic retrofitting. For that reason, several researchers have proposed various stress-strain models for describing the behavior of concrete confined with FRP jackets. It is worth mentioning that most of the existing models have been developed to improve or modify the analytical result of Richart's tests on concrete cylinders subjected to fluid pressure. However, in these models, confined compressive strength is predicted without a failure criterion of concrete under multiaxial stress state with the exception of the ones adopting Mander model developed for concrete confined with transverse steel reinforcement. As a preliminary study, the stress-strain relations of some of the experimentally tested RC columns confined with CFRP jackets are successfully predicted adopting Koksal model introducing a new failure criterion of concrete under triaxial compression. This model had been previously developed for RC columns confined with conventional reinforcement of steel.
Keywords: compressive fracture; confinement; reinforced concrete column; FRP jackets; stress-strain relation; failure criterion; CONCRETE COLUMNS; FIBER; STRENGTH; BEHAVIOR; MEMBERS; Construction & Building Technology; Engineering